(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Physical activity on prescription (PAP) programmes have demonstrated a positive impact on health, wellbeing, and physical activity levels. However, such programmes face both structural and organisational barriers. In Belgium, PAP programmes are implemented in various forms. In Flanders, a regional programme centred on physical activity counselling was established; whereas in Wallonia, multiple decentralised initiatives co-exist, with a primarily focus on adapted physical activity. In 2023, a national network was established to foster synergies among existing initiatives and enable stakeholders to gain a better understanding of the PAP ecosystem. One of the objectives of this network was to develop potential models for a harmonised PAP framework in Wallonia and, therefore, in Belgium. Methods: A working group was formed based on the national network of PAP initiatives, and a non-systematic narrative review of PAP was carried out, focusing specifically on four prescription-based systems in Europe. Sources included peer-reviewed articles, grey literature, and policy documents retrieved through targeted searches. Key structural elements that could be further explored, refined, and operationalised within a working group were identified through expert consultation. Additionally, key areas where further research is needed to inform both practice and future programme development were also highlighted. Results: When already well-documented or experienced in existing programmes, facilitating a capitalisation on current practices, some structural elements of PAP were prioritised to be explored and refined by the working group. These structural elements were: the categories of prescribed physical activity and their definitions, the prescribers, the beneficiaries; the physical activity professional, their roles and training. Gaps in the literature and further research specific to Wallonia context were also identified. Conclusion: Despite the limitations of narrative reviews, this study serves as a rapid preliminary assessment that can facilitate the consolidation of expertise and the capitalisation on existing PAP initiatives. This initial overview provides a foundation for structuring existing PAP and for identifying future research directions that can enhance their practical implementation. Support/Funding Source: This study was conducted in collaboration of the Expertise Centre in Health Promotion in Sciensano, funded by l’Agence pour une Vie de Qualité, Department Zorg and Vivalis.